2019
DOI: 10.1161/circgen.119.002656
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Blood RNA Levels of QSOX1 and PLBD1 Are New Independent Predictors of Left Ventricular Dysfunction After Acute Myocardial Infarction

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…In addition, the expression level of IL18R1 is significantly altered in systemic and arterial bed-dependent atherosclerosis plaques (27). IL18R1 is upregulated in patients with acute ST elevation MI (28,29). In this study, we first found the association between AC005392.3, AC007278.2, and IL18R1.…”
Section: Discussionmentioning
confidence: 62%
“…In addition, the expression level of IL18R1 is significantly altered in systemic and arterial bed-dependent atherosclerosis plaques (27). IL18R1 is upregulated in patients with acute ST elevation MI (28,29). In this study, we first found the association between AC005392.3, AC007278.2, and IL18R1.…”
Section: Discussionmentioning
confidence: 62%
“… 58 , 59 A recently study reported that the peripheral blood level of QSOX1 related to neutrophil infiltration is a novel independent predictor of left ventricular dysfunction. 60 …”
Section: Discussionmentioning
confidence: 99%
“…58,59 A recently study reported that the peripheral blood level of QSOX1 related to neutrophil infiltration is a novel independent predictor of left ventricular dysfunction. 60 To date, the clinical value of ARG1, CKAP4, C3AR1, ELANE, GGH, ORM1, and QSOX1 in burn shock has not been documented. From the above description, we know that ARG1, C3AR1, ELANE, and ORM1 are released from activated neutrophils and have different effects on immune response.…”
mentioning
confidence: 99%
“…The patient study protocol complied with the Declaration of Helsinki, was approved by the regional ethical committee, and all patients signed informed consent (Ethical Committee ML8525, Belgian trial no. B322201214942, S54129) ( 7 ).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we investigated the temporal changes in transcriptional profile of patients with an acute myocardial infarction (AMI) in circulating blood cells ( 7 ). We confirmed a robust activation of pro-inflammatory pattern recognition receptors, including the C-type lectin domain family 4 member E receptor (CLEC4E) that is usually expressed on leukocytes and activated in response to bacteria ( 8 , 9 ).…”
mentioning
confidence: 99%